Comparative evaluation of plasma and serum HIV-1 viral load measurements among HIV positive individuals, Northwest Ethiopia: Analytical cross-sectional study - Getu Girmay; Habtam Alemu; Muluneh Assefa; Nega Birhane; Mulualem Lemma (PLoS ONE, 2025)
Introduction Plasma HIV viral load tests have been widely used in clinical practice to monitor treatment success or failure. Inappropriate mixing with anticoagulants and inaccessibility of plasma samples in certain clinical services (such as antenatal care services) might hinder HIV diagnosis and treatment services. Considering that serum has higher stability and availability in prenatal care services, periodic monitoring of serum HIV viral load might be an alternative approach. Thus, this study aimed to evaluate the plasma and serum HIV-1 viral load measurements among HIV-positive individuals in Northwest Ethiopia. Methods An institution-based analytical cross-sectional study was conducted on 74 paired plasma and serum samples from May to August 2020 at the HIV Treatment Center, Northwest Ethiopia. Four milliliters of paired venous blood were collected to harvest plasma and serum. HIV-1 RNA was extracted and quantified using the Roche COBAS AmpliPrep/COBAS TaqMan assay. Data were analyzed using SPSS version 20. Paired sample t-tests and Pearson’s correlation were employed to observe the mean differences and associations between sample measurements, respectively. Bland–Altman and linear regression models were computed to demonstrate the level of agreement and proportional bias, respectively. A p-value of ≤  0.05 with a 95% confidence interval was considered statistically significant. Results From a total of 74 HIV-positive individuals, 49 (66.2%) were females. The mean ±  SD age was 36.3 (10.1) years. The mean difference ±  SD of plasma and serum HIV-1 viral load was 0.07 ±  0.75 log copies/mL, (p =  0.428). A strong association with a significant linear correlation (r =  0.862) (p < 0.001) and a high level of agreement were observed between the sample measurements using Pearson’s correlation and a Bland–Altman plot, respectively. Conclusions The current study highlights an alternative application of serum-based HIV viral load quantification to enhance the rate of HIV diagnosis and treatment monitoring coverage.